CORRELATION OF SERUM CARBAMAZEPINE AND GAMMA GLUTAMYLE TRANSFERASE IN ADULT EPILEPTICS - Malghani, Akhtar Hamid; Tayyab, Muhammad; Ditta, Allah; Chaudhry, Haroon Rashid; Saleem, Mohammad; Din, Haleem -ud-; Chaudrhy, Naseer Ahmad (Journal of Ayub Medical College Abbottabad, 1998)
A study was conducted to determine serum carbamazepine (CBZ) levels by high performance liquid chromatography (HPLC) and gamma glutamyl transferase (GGT) activity in 40, already diagnosed epileptic patients (20 males and 20 females) on CBZ therapy for more than six months. Twenty normal healthy controls (JO males and 10 females) were included in the study. The mean f standard deviation of CBZ level in all subjects, males (young and old, females young and old) were 4.2±2.76, 3.47±2.15, 3.65±3.21 and 4.80±^3.27, 3.86 f 3.65 ug/ml respectively. While the GGT level in all the subjects were 50.57±23.36, in male 52.42 ±23.68 IU/L and in female 48.5±23.28 IIJ/L. It was observed that the serum GT activity> in relation to daily- dosage of CBZ was more in old than young groups. The comparison between daily dosage and CBZ was weakly positive (r- 0.2951) while serum CBZ versus serum GGT activity (0.09820), shows no correlation. Hence it was concluded that there is no significant correlation between serum CBZ level and serum GGT activity. To avoid toxic effects of drug over dosage and to obtain therapeutic results drug monitoring is essential.